Immobilization of ruthenium phthalocyanine on silica-coated multi-wall partially oriented carbon nanotubes: Electrochemical detection of fenitrothion pesticide - Canevari, Thiago C.; Prado, Thiago M. [UNESP]; Cincotto, Fernando H. [UNESP]; Machado, Sergio A. S. [UNESP] (Elsevier B.V., 2016)
This paper reports on the determination of the pesticide fenitrothion using a glassy carbon electrode modified with silica-coated, multi-walled, partially oriented carbon nanotubes, SiO2/MWCNTs, containing ruthenium phthalocyanine (RuPc) synthesized in situ. The hybrid SiO2/MWCNTs/RuPc material was characterized by UV-vis absorption spectroscopy, X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HR-TEM) and differential pulse voltammetry. The modified electrode showed well-defined peaks in the presence of fenitrothion in acetate buffer, pH 4.5, with a sensitivity of 0.0822 mu A mu M-1 mm(-2) and a detection limit of 0.45 ppm. Notably, the modified SiO2/MWCNTs/RuPc electrodes with did not suffer from significant influences in the presence of other organophosphorus pesticides during the determination of the fenitrothion pesticide. Moreover, this modified electrode showed excellent performance in the determination of fenitrothion in orange juice. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Composites; Nanostructures; Sol-gel chemistry; Electrochemical measurements; Catalytic properties